BIT ERROR RATE PERFORMANCE OF CASCADED OPTICAL AMPLIFIERS USING MATLAB COMPUTATION SOFTWARE - Kelvin, Benjamin Ayibapreye; Afa, John Tarilanyo (European Scientific Journal, ESJ, 2013)
This paper gives a detailed presentation of the bit error rate (BER) performance of cascaded optical amplifiers with variation of amplified spontaneous emission noise in an optical network using Matlab files that models the transmission of an on-off keyed non-return to zero (NRZ) optical signal through a cascade of optical amplifiers (typically Erbium Doped Fibre Amplifiers (EDFAs) separated by optical loss (i.e. fibre) and calculate the amplified spontaneous emission (ASE) noise, optical-signal-to-noise ratio (OSNR), Q factor and BER at the amplifier input and output, fibre dispersion was accounted for by a penalty on Q. Matlab computer program was used to model the design and calculation of ASE noise, OSNR, Q factor, BER and penalty in Q were made. The performance of the receiver as a function of OSNR and received ASE PSD, BER and other output parameters was investigated.